STATISTICAL ANALYSIS OF FACTORS OF HOUSING IMPROVEMENT FOR URBAN AND RURAL POPULATION OF THE ORENBURG REGION - T. N. Larina; A. N. Kibataeva (Статистика и экономика, 2018)
Living conditions refer to the main characteristics that determine the level and quality of life. Living conditions in Russia are differentiated according to the levels of family income, family structure, location of residence and other factors. The relevance of the study of living conditions in the context of urban and rural areas increases with the growing necessity of creating the basis for social development in our country (“State program of development of agricultural industry, and of raw material and foodstuff market for 2013–2020”, approved by the Resolution of the Government of the Russian Federation of July 14, 2012, No. 717). The analysis of factors that contribute to the change of population’s living conditions depending on the type of the settlement (a city, a rural area), significantly clarifies the tendencies of the economic and demographic processes that take place in Russia (for example, the reasons of the population migration from rural settlements into cities, the instability of agricultural production etc.).The purpose of the study is to identify the most significant socio-economic factors that determine the changes of housing conditions of the urban and rural population of the region. The urban and rural households of the Orenburg region are the subject of research.The materials and methods of the study. The information base of research includes the data of household budget survey, made by Orenburgstat. The information was detailed in the context of urban and rural areas in the period from 2003 to 2016. The authors comparatively analyzed the level and the structure of disposable household resources, consumer spending and other indicators that were relevant for rural and urban households of the Orenburg region. The authors gave a quantitative assessment of the impact of the structure of consumer spending and disposal resources of households and demographic factors on the level of provision of comfortable housing for urban and rural households. The choice of a modified statistical correlation coefficient was motivated by the fact that the initial data array consists of time series, some of which are non-stationary time series. The usage of a modified correlation coefficient allows the exclusion of the auto-correlation influence effects, therefore providing us with the objective estimate of the interrelationships in the dynamics.The research results showed that the factors, determining the change in the level of comfortable household provision are different for the urban and rural population. For example, the rural households are not as heavily affected by the increase of utility fees (water, sewerage, gas, electricity) in the context of the growth of the comfortable housing provision. The improvement of living conditions of urban households in the Orenburg region is associated with the family structure change, increased life expectancy as well as with the increase in the proportion of houses in renting.The conclusion. Taking into account the differentiated impact of factors on urban and rural households, the state must direct the efforts on social development of rural areas and on the improvement of rural population’s living conditions. This will allow the development of domestic agriculture and will reduce the demographic losses in rural areas that were caused by the urbanization and declined living standards.